Fibre optic sensing for measuring rotor blade structural dynamics. - Weber, Simone (Cranfield University, 2019)
Researchers and practitioners spend much e ort in developing theoretical methods to design and predict the performance of helicopter rotor blades. These blades have evolved to become complex structures designed to operate in extreme conditions and over the exceptionally broad flight envelopes of helicopters. As a result, these vehicles are subject to strict maintenance regimes that increase the overall operational costs. The need to reduce such costs and improve aircraft performance together with the emergence of novel fibre optic-based sensor technologies form the context of the research presented in this thesis. Opportunities for blade health and usage monitoring created by sensor technologies such as fibre Bragg gratings (FBG) for measuring strain and direct fibre optic shape sensing (DFOSS) present today's industry with a critical question: Does the designer follow contemporary technological trends and adopt a preventative approach where he/she invests in such instrumentation systems or is a reactive approach more appropriate where he/she awaits to have sufficient evidence of operational need? A survey was carried out as part of this research to understand this dichotomy faced by rotorcraft engineers and systems architects. Adhering to the safety orientated culture within the aerospace community, the aim of this research work is the numerical and experimental exploration of challenges associated with the deployment of fibre optic instrumentation systems for future health and usage monitoring. This was achieved through three objectives: (1) development of a computational framework allowing the simulation of rotor blade dynamics at an appropriate fidelity, (2) exploration of blade health monitoring capabilities using fibre optic instrumentation systems and, (3) laboratory-based structural testing. Health and usage monitoring capabilities were explored theoretically through a parametric damage study using the computational framework. The experimental testing highlighted the need for a sensor placement methodology for distributing FBG-based strain sensors over the blade (both in terms of spanwise and chordwise locations) for accurately recovering mode shapes. This was followed by investigating the accuracy of the novel DFOSS system by deploying it on a bearingless main rotor blade along with other commercially available instrumentation systems. Test results were used to (1) perform multi-step indirect finite element modelling to increase the accuracy of the developed structural model and, (2) to explore the suitability of FBG and DFOSS measurements for damage detection. The main finding of this work is that future rotor health and usage monitoring systems based on fibre optic sensing technologies require the development of a hybrid FBG and DFOSS instrumentation system. Although numerous areas of further work have been identified, it is hoped that the adoption of such an instrumentation system will not only help reduce operational costs but also provide much needed operational data on helicopter blade dynamics to validate methods and improve designs.
Keywords: Bearingless main rotor; health monitoring; fibre optic sensors; shape sensing; helicopter dynamics; damage detection